A study on olfactory improvement assessed with butanol threshold test in chronic rhinosinusitis patients after fess at a tertiary care centre in Malabar region - K. K., Adheela Nusrin; Kizhakkethil, Ramachandran; Menon, Ashwin M.; Jacob, Amal John; Varghese, Bindu Sara; Saleem, Thasneem (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2023)
Background: Chronic Rhinsinusitis is a hetreogenous disorder with a broad range of etiologic factors involving mucosa of nasal cavity and paranasal sinuses. Olfactory dysfunction has been reported in approximately 60-80% of patients who suffer from CRS. Methods: Hospital based prospective observational study in the department of ENT, KMCT medical college, Mukkam done in Patients diagnosed with CRS who require FESS having anosmia or hyposmia as an additional symptom. Calculated sample size was 87. Butanol threshold test was done in patients before undergoing FESS and at 1st week,6th week and 24 weeks following FESS and improvement noted. Independent sample t test and ANOVA were used to test statistical significance Results: Out of 87 subjects, 36% belonged to age group of 36-45 years 15-25 years was the least involved group and majority of patients had nasal obstruction (83.9%) or nasal discharge (81.6%). 69% of patients experienced facial pain and 79.3% had post nasal discharge. Pre operative BTT showed a mean value of 4.89.BTT at 1st week post op showed a mean value of 3.63. At 6 weeks post op BTT value showed significant difference from pre op value with a mean of 2.05 and at 24 weeks post op the mean BTT was 1.70 Conclusions: Summarising the results from our study we affirm that FESS improves olfactory function substantially in CRS patients especially in patients with polyps.